2021
DOI: 10.1016/j.artd.2021.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the 30-day mortality burden after revision total knee arthroplasty

Abstract: Background: In revision total knee arthroplasty (TKA), information regarding perioperative mortality risk is essential for careful decision-making. This study aimed to elucidate the (1) overall 30-day mortality rate and (2) 30-day mortality rate stratified by age, comorbidity, and septic vs aseptic failure after revision TKA. Methods: The American College of Surgeons National Surgical Quality Improvement Program was reviewed for all patients undergoing revision TKA from 2011 to 2019. A total of 32,354 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Another study showed similar rates for primary THAs (0.29%) and revision THAs (0.30%) 26 . The mortality rates of primary TKAs (0.098%) and revision TKAs (0.36%) were similar 27,28 .…”
Section: Discussionmentioning
confidence: 83%
“…Another study showed similar rates for primary THAs (0.29%) and revision THAs (0.30%) 26 . The mortality rates of primary TKAs (0.098%) and revision TKAs (0.36%) were similar 27,28 .…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, these results may not be applicable to patients with a high perioperative mortality risk. This limitation is notable given that the mortality risk after an rTKA is not insignificant, especially for patients undergoing a septic rTKA and those with a greater comorbidity burden, both of which are more common in patients with HCV [ 27 , 32 , 33 ]. Additionally, the possibility of coding errors is inherent with any analysis of administrative claims data.…”
Section: Discussionmentioning
confidence: 99%
“…5,7 Despite mortality being the most feared and devastating outcome associated with rTHA, there is a paucity of literature characterising inpatient mortality rates associated with the procedure especially when compared to studies in total knee arthroplasty. 27,28 Furthermore, there is limited data quantifying changing trends in mortality rate when looking at septic and aseptic indications for revision surgery. Our study found an overall inpatient mortality rate of 0.91% when all indications for revision surgery were considered.…”
Section: Discussionmentioning
confidence: 99%